Education, Technology, and the Characteristics of Worker Productivity. - Gintis, Herbert (American Economic Review, 1971)
Economists have long noted the relationship between the level of schooling in workers and their earnings. The relationship has been formalized in numerous recent studies of the rate of return to schooling and the contribution of education to worker productivity. Almost no attempt has been made, however, to determine the mechanism by which education affects earnings or productivity. In the absence of any direct evidence, it is commonly assumed that the main effect of schooling is to raise the level of cognitive development of students and that it is this increase which explains the relationship between schooling and earnings. This view of the schooling-earnings linkage has provided the conceptual framework for studies which seek to control for the quality of schooling through the use of variables such as scores on achievement tests and IQ. [26, 46] The objective of this paper is to demonstrate that this interpretation is fundamentally incorrect. It will be seen that rejection of the putative central role of cognitive development in the schoolingearnings relationship requires a reformulation of much of the extant economic research on education, as well as a radical rethinking of the normative bases of the economics of education in particular, and neo-classical welfare economics in general. In Section I, I will present data to suggest that the contribution of schooling to worker earnings or occupational status cannot be explained by the relationship between schooling and the level of cognitive achievement. Indeed, the data there introduced strongly suggest the importance of noncognitive personality characteristics which have direct bearing on worker earnings and productivity. In Section II, I will give substantive content to the relevant personality variables operative in the relationship between education and earnnings. With the theoretical literature on the personality requisites of adequate roleperformance in a bureaucratic and hierarchical work-enrivonment as a frame of reference, I will sketch some mechanisms through which schools affect earnings. This involves scrutinizing the social relations of education and the pattern of rewards and penalties revealed in grading practices. I will argue that the authority, motivational, and interpersonal relations codified * This research was supported by a grant from the Carnegie Foundation of New York to the Center for Educational Policy Research, Harvard Graduate School of Education, and a separate grant from the Social and Rehabilitation Service, U. S. Dept. of Health, Education, and Welfare. Special thanks are due to Stephan Michelson, Christopher Jencks and Samuel Bowles, who aided the research through its various stages, and the Union for Radical Political Economics collective at Harvard, whose members helped broaden its scope. This work is part of a larger project in process jointly with Samuel Bowles, on the political economy of education. The arguments presented herein have been significantly abridged, in conformance with stringent space limitations. Requests for amplification of the material should be addressed to the author.